An adult case of Kommerell's diverticulum with a right-sided aortic arch. (May 2017) - Tsutsumi, Koji; Nishida, Kosuke; Tsukamoto, Jun; Iijima, Natsumi; Ishida, Osamu
The patient was a 56-year-old woman with Kommerell's diverticulum associated with a right-sided aortic arch with mirror-image branching. No other congenital heart anomalies or vascular rings were observed. Descending aortic replacement through a right posterolateral thoracotomy was performed to eliminate the risk of diverticular rupture. The patient's postoperative course was uneventful. This was a rare adult case of right-sided aortic arch with Kommerell's diverticulum associated with no other congenital heart disease.